Foraging Behaviour of Three Shorebird Species on Coastal Mudflats of Southwestern Sarawak - Ng, Wen Teng; Mohamad Fizl Sidq, Ramji; Jongkar, Grinang; Andrew Alek, Tuen (The Malaysian Society of Applied Biology, 2024)
Many shorebirds are long-distance migrants and they congregate on intertidal mudflats for feeding throughout their non-breeding season. Despite being one of the key staging sites for migratory shorebirds, data on shorebirds foraging ecology in Sarawak is insufficient for the understanding of the interaction between shorebirds and their behaviour. This study aimed to determine the foraging behaviour of Whimbrel (Numenius phaeopus), Bar-tailed Godwit (Limosa lapponica) and Terek Sandpiper (Xenus cinereus) at Asajaya and Buntal mudflats. Data collection of this study was conducted at low tide, during two non-breeding seasons with a total of 12 months of sampling. Focal observations were conducted within a 50 m × 50 m quadrat. A total of 8 exclusive foraging techniques were observed for the three shorebird species, including: pecking, probing, picking, stabbing, snapping, submerging, sweeping and ingesting. Terek Sandpiper displayed all the exclusive foraging behaviours, whereas Whimbrel and Bar-tailed Godwit showed 7 and 5 behaviours, respectively. The three shorebirds also displayed non-exclusive foraging behaviours such as walking, preening and defecating. Spearman correlation test indicates a positive correlation between the foraging behaviours performed among three shorebird species. All three shorebird species adopted similar mixed foraging strategies comprising pecking and probing, with an exception on supplementary behaviours observed in Whimbrel and Terek Sandpiper. Principal Component Analysis (PCA) analysis showed a strong correlation between picking and ingesting behaviours, suggesting a high chance of foraging success with the presence of picking behaviour. The outcome of this study is crucial in understanding how shorebirds maximise their behavioural performance when foraging as well as to assist in formulating better conservation strategies for targeted migratory shorebird species and coastal mudflats.